Life expectancy estimations and determinants of return to work among cancer survivors over a 7-year period - Wei-Liang Chen (Nature Portfolio, 2021)
Abstract Due to advances in medical science and technology, the number of cancer survivors continues to increase. The workplace needs and employment difficulties cancer survivors face after treatment need to be addressed to protect these individuals’ right to work and to maintain the overall labor force of the country. We conducted a retrospective cohort study with a follow-up period from 2004 to 2010. All data analyzed in the study were obtained from the Labor Insurance Database, the Taiwan Cancer Registry of the Ministry of Health and Welfare, and the National Health Insurance Research Database. The relationships between risk factors and the presence of returning to work were analyzed by a Cox proportional hazard model. The survival rates of patients with different cancer stages were evaluated using Kaplan–Meier survival analysis. Among the employees with an initial diagnosis of cancer, 70.4% remained employed through 1 year after the diagnosis, accounting for 83.4% of all cancer survivors; only 51.1% remained employed through 5 years after the diagnosis, accounting for 78.7% of all cancer survivors, a notable decrease. Age, gender, salary, treatment method, company size, and cancer stage were the factors that affected whether employees could return to work or not. The long-term survival of people diagnosed with cancer depends on their chances of returning to work. Strengthening existing return-to-work policies and assisting cancer survivors with returning to work after the treatment should be priorities for protecting these individuals’ right to work and for maintaining the overall labor force.